Rekonstruksi Etika Ekologis dalam Hadis sebagai Respon Terhadap Krisis Iklim Global - Muhammad Azzam; Tajul Arifin (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
Purpose: This study aims to analyze the concept of al-Jarḥ wa al-Ta'dīl from the perspectives of Ahlus Sunnah and Syi'ah Imamiyyah, as well as to examine the methodological and epistemological differences between the two traditions, particularly in relation to the construction of religious authority in Islam. Method: This study employs a qualitative approach with a library research design and a thematic-comparative (maudhu'i) method. Data were collected through documentation of primary and secondary sources, including major hadith collections, rijal literature, and relevant academic journal articles, and analyzed using a descriptive-analytical technique. Results: The findings indicate that Ahlus Sunnah evaluates narrators based on 'adālah (moral integrity) and ḍabṭ (accuracy) within an objective-historical framework, while Syi'ah Imamiyyah integrates these criteria with a theological framework centered on the authority of the Ahlul Bayt. These differences are not merely methodological but also epistemological, as evidenced by divergent interpretations of the Hadith of Ghadir Khum and the Hadith of the Twelve Caliphs. This study contributes to the enrichment of hadith studies and encourages a more objective understanding of inter-sectarian differences in Islamic scholarship.